Técnica para determinar cáncer cérvico-uterino en mujeres de los barrios suburbanos de la ciudad de riobamba atendidas en la unidad oncológica provincial solca de chimborazo a través de su programa plan vida - Coba Llanda, William Patricio (2010)
The work described below is about the Life Plan project through which was supportive of women in the suburbs of the city of Riobamba a chat about the early detection of cancer and Pap making the same to be analyzed in the cytology laboratory of the United Oncology SOLCA de Chimborazo